Pelatihan Bacaan Idzhar Pada Al-Qur’an Juz 30 Bagi Jama’ah Musholla Di Perumahan Grand Mulia, Kalisuren - Muhammad Soleh Ritonga; Fery Rahmawan Asma; Fajar Erlangga; Nur Ali (CV. Multi Kreasi Media, 2025)
Idzhar is one of the recitation rules frequently found in Al-Qur’an. Therefore, proper understanding and practice are essential to ensure that verses containing this rule are recited correctly and in accordance with Tajwid principles. However, many people remain unfamiliar with Idzhar, both in theory and practice. This was observed among the congregation of Musholla Al-Jihad, Grand Mulia Kalisuren Housing Complex, Tajurhalang, Bogor. Observations revealed that most members of the congregation were still unable to apply the Idzhar rule accurately in their recitation. To address this issue, the Community Service (Adbimas) team conducted a training program on Idzhar recitation in Juz 30 of Al-Qur’an for the congregation of Musholla Al-Jihad. The program aimed to provide theoretical explanations while simultaneously developing participants’ practical skills in applying Idzhar. During the sessions, the congregation responded positively and gradually improved their ability to recite Idzhar correctly. This activity is expected not only to enhance the quality of the congregation’s Al-Qur’an recitation during and outside sholat but also to contribute to strengthening religious literacy within the community.